INOVASI TEKNOLOGI DALAM KEWIRAUSAHAAN: MEMBANGUN EKOSISTEM BISNIS BERKELANJUTAN MELALUI PELATIHAN KEWIRAUSAHAAN DIGITAL - Jana Sandra; Muhammad Iqbal Firdaus; Prima Widiyanto; Rahmani Fitra (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
Technological innovation in entrepreneurship is increasingly playing an important role in building a sustainable business ecosystem. This research aims to explore the impact of digital entrepreneurship training on business sustainability, especially for micro, small, and medium enterprises (MSMEs). Using a qualitative approach with a case study method, data was collected through in-depth interviews, participatory observations, and analysis of related documents. Purposive sampling techniques are used to ensure that respondents have relevant experience in the application of digital technology in their business. The results of the study show that digital entrepreneurship training contributes significantly to increasing digital literacy, expanding market reach, and accelerating technology adoption among entrepreneurs. In addition, the sustainability of MSME businesses is greatly influenced by support from the government, the private sector, and educational institutions, especially in terms of providing technological infrastructure, access to continuous training, and business assistance. As a recommendation, this study emphasizes the importance of developing a digital entrepreneurship training curriculum that is more adaptive and based on the specific needs of entrepreneurs. In addition, expanding access to this training is a strategic step to ensure that more MSMEs can make optimal use of technology. Thus, technological innovation in entrepreneurship is expected to continue to develop and have a positive impact on sustainable economic growth.